An investigation on MX/G/1 queuing model of interrupted services in the manufacturing of edible cutlery process. (10th January 2023) - Vignesh, P.; Srinivasan, S.; Sundari, S. Maragatha; Eswar, S. Kishore
We are investigating queuing issues that happen during the cutlery production process hour in this study. Plastic is widely used all around the world as it is simple to manufacture and inexpensive to purchase. Banana leaves are commonly used to wrap food in hotels. Plastic is widely used to replace banana leaves since it is affordable and lightweight. Research on biodegradability of plastics did not succeed. Hence, researchers set out to design alternative hardwood cups and spoons for food and beverage applications. A lengthy step-by-step process is required to create this edible millet cutlery. This process is converted into a scientific queuing model and solved with supplementary variable queuing technology. For the defined queue study, the probability generating function for queue size and all other performance measures are determined. In order to validate the model at the conclusion, the conceptual study of queue theory in the creation of edible cutlery is depicted through a numerical and complex visual analysis.